Applying Communicative Language Teaching in Science Instruction - Agao-Agao, Ana Margarita Abogadil; Guiali, Jamaica M.; Madi, Huda A.; Agao-Agao, Allan M (RIRAI Publisher, 2025)
This study aimed to determine the impact of Communicative Language Teaching (CLT) approach in the engagement and understanding of science concept of Grade 8 students at Integrated Laboratory Science High School of Mindanao State University-Maguindanao school year 2023-2024. It sought answer to the following research problems; what are the pretest and posttest scores of the respondents in role playing, graphic organizer, word hunts, broadcasting and dramatization? and Is there a significant difference between the pretest and posttest scores of the respondents in role playing, graphic organizer, word hunts, broadcasting and dramatization? This study is quantitative in nature, a one-group pretest-posttest design. The researcher – made 75 items test questions was the instrument used to gather the data before and after the two - months intervention. Results showed the pretest grand mean score 8.05 described as good and the posttest score 11. 37 described as very good. The t-test results revealed a p-value 0.000 with significant difference at 0.05 level of significance. Thus, there is enough evidence to reject the null hypothesis that there is no significant difference between the pretest and posttest of the respondents. Based on the results, it is concluded that the intervention, CLT approach in teaching Science has positive impact on the respondents’ performance in improving their engagement and understanding the concept. Strategies like roleplaying, graphic organizer, word hunts, broadcasting and dramatization help the respondents use English language in the class activities and improve their linguistic competence.